2008
DOI: 10.1124/mol.108.050161
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Dependent Reactive Oxygen Species-Mediated Programmed Cell Death Induced by 3,3′-Diindolylmethane through Inhibition of F0F1-ATP Synthase in Unicellular Protozoan ParasiteLeishmania donovani

Abstract: Mitochondria are the principal site for the generation of cellular ATP by oxidative phosphorylation. F0F1-ATP synthase, a complex V of the electron transport chain, is an important constituent of mitochondria-dependent signaling pathways involved in apoptosis. In the present study, we have shown for the first time that 3,3Ј-diindolylmethane (DIM), a DNA topoisomerase I poison, inhibits mitochondrial F0F1-ATP synthase of Leishmania donovani and induces programmed cell death (PCD), which is a novel insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 42 publications
3
122
0
4
Order By: Relevance
“…ROS overproduction in Leishmania is frequently associated with programmed cell death processes through mitochondrial dysfunction (37). The decrease in intracellular L. pifanoi parasites was also confirmed by electron microscopy.…”
Section: Damage To the Mitochondria Of L Donovani Promastigotes Causmentioning
confidence: 62%
“…ROS overproduction in Leishmania is frequently associated with programmed cell death processes through mitochondrial dysfunction (37). The decrease in intracellular L. pifanoi parasites was also confirmed by electron microscopy.…”
Section: Damage To the Mitochondria Of L Donovani Promastigotes Causmentioning
confidence: 62%
“…In addition to its antitumor effects, DIM has also been recognized to specifically target L. donovani topoisomerase I (16). Moreover, we recently demonstrated that DIM induces programmed cell death through the inhibition of mitochondrial F o F 1 ATP synthase in the unicellular protozoan parasite L. donovani and reduces the parasitic loads in the livers and spleens of infected hamsters (17). Thus, DIM could be of interest in the treatment of human leishmaniasis.…”
Section: 3-diindolylmethane (Dim) a Novel Poison Targeting Leishmamentioning
confidence: 99%
“…The effect of the drug on the viability of the WT and LdDR50 cell lines was determined by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (17). The cells were collected at the exponential phase and transferred to a 24-well plate (2 ϫ 10 6 cells per well).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are particularly susceptible to such a damage caused by ROS that are continuously generated by the mitochondrial respiratory chain 44 . The generation of ROS can also be induced by certain drugs, affecting parasite mitochondrial functions [45][46][47][48] . The same principle worked for BenzCo in killing parasites.…”
Section: In Vitro Antileishmanial Activitymentioning
confidence: 99%